2022
DOI: 10.14192/kjicp.2022.27.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Infection Control of Severe Fever with Thrombocytopenia Syndrome in Korea

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne infectious disease caused by a novel Dabie bandavirus belonging to the genus Bandavirus. The incidence of SFTS has been increasing in East Asia, posing a great concern to public health in endemic areas. Although SFTS has a high case-fatality rate, there is currently no effective treatment for SFTS. Therefore, early diagnosis and prevention of SFTS are essential. Primarily, SFTS is a tick-borne zoonosis, but human-to-human transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Although SFTS cases have been reported across South Korea, most occur in grassy, brushy, or wooded areas suitable for ticks, including Gyeonggi, Gangwon, and Gyeongbuk [ 19 ]. Notably, agricultural farmers, who have occupational risk factors associated with SFTS [ 12 , 20 , 21 ], are most likely to be exposed to ticks infected with Dabie bandavirus .…”
Section: Discussionmentioning
confidence: 99%
“…Although SFTS cases have been reported across South Korea, most occur in grassy, brushy, or wooded areas suitable for ticks, including Gyeonggi, Gangwon, and Gyeongbuk [ 19 ]. Notably, agricultural farmers, who have occupational risk factors associated with SFTS [ 12 , 20 , 21 ], are most likely to be exposed to ticks infected with Dabie bandavirus .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of sex ratio, SFTS incidence was more common in the men included in this study. However, in Korea, SFTS was reported to be more prevalent in women [ 19 ]. Other studies, particularly from China, also reported that SFTS incidence was more common in women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from the KDCA during 2013–2021, SFTSV infections in Jeju Island occurred mainly during the spring and summer seasons, in contrast with regions in the mainland, where SFTSV incidence was high during autumn. 20 Therefore, summer presents a high risk of SFTSV human infection in Jeju Island.…”
Section: Discussionmentioning
confidence: 99%